2018
DOI: 10.1007/s11739-018-1960-5
|View full text |Cite
|
Sign up to set email alerts
|

The pathogenetic mechanisms of cough in idiopathic pulmonary fibrosis

Abstract: Idiopathic pulmonary fibrosis is a peripheral subpleural interstitial lung disorder limited to the lung not involving the airways. It has a poor prognosis (survival less than 5 years) and commonly an interstitial pneumonia radiological pattern. Patients complain of a chronic dry cough in 80% of cases. A cough is often the first symptom of this rare disease, preceding dyspnea by years, and is associated with a poor prognosis, high dyspnea scores and low FVC percentages. The pathogenetic mechanisms leading to co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 50 publications
1
15
0
Order By: Relevance
“…25 Salivary pepsin level can quickly distinguish true reflux with non-reflux diseases, and is important for the diagnosis of GERD patients with predominant respiratory symptoms. [14][15][16][17]26 In this study, the positive rate of detecting EES was 68.2%, which was consistent with the observation of a previous study, 24 suggesting that salivary pepsin is of certain diagnostic value for the diagnosis of EES. In addition, the salivary pepsin level and positive rate in the BE group were significantly higher than those in the HC group in the present study, suggesting that pepsin reflux does play a significant role in the process of BE formation.…”
Section: Discussionsupporting
confidence: 91%
“…25 Salivary pepsin level can quickly distinguish true reflux with non-reflux diseases, and is important for the diagnosis of GERD patients with predominant respiratory symptoms. [14][15][16][17]26 In this study, the positive rate of detecting EES was 68.2%, which was consistent with the observation of a previous study, 24 suggesting that salivary pepsin is of certain diagnostic value for the diagnosis of EES. In addition, the salivary pepsin level and positive rate in the BE group were significantly higher than those in the HC group in the present study, suggesting that pepsin reflux does play a significant role in the process of BE formation.…”
Section: Discussionsupporting
confidence: 91%
“…IPF is one of the late outcomes of lung diseases, induced by a variety of causes, that is characterized by destruction of the alveolar histoarchitecture, excessive accumulation of extracellular matrix, infiltration of immunocytes, and irregular changes in fibroblasts (Martinez et al, 2017). As a chronic, progressive, fibrosing form of interstitial pneumonia, IPF reduced human survival, which has been historically approximately 50% with an average survival duration of fewer than 5 years (Bargagli et al, 2019; Lancet, 2015). Studies have suggested that the EMT (epithelial‐mesenchymal transformation) process, characterized by loss of epithelial markers and gain of mesenchymal markers, might account for the occurrence of fibrosis (Qian, Lin, Zhao, Wang, & Liu, 2018; Zhang et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…A further study found no association between GORD and cough in patients with IPF [3]. Therefore, the impact and association of GORD with cough may be weaker in patients with IIPs than in those with CTD-ILD, even though GORD is thought to be involved in the pathogenesis of IIPs [32].…”
Section: Discussionmentioning
confidence: 90%